Labour skills and culture university researchers. Coopetition networks (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2010)
This dissertation is a reflection, supported by two previous investigations by the writer, the aim is to relate the work skills required by the working environment in Latin America and the responses from the Venezuelan higher education can lead to a changing environment, to articulate these results Approximate diagnosed with university research culture. Then we present a proposal to provide college and environment linkages, and favors a relationship of cooperation and competition between the requirements of the workplace, the skills of university graduates and university research praxis. The method applied to investigations that give rise to this article are focused on: a) review of documents concerning the study (job skills and environment) and b) the hermeneutic interpretation of the data collected through interviews with key informants and the review and analysis literature. In conclusion arises: a) the need to prevail in the Venezuelan university proactive in its relationship with the environment, b) to replace a research culture focused Orthodox culture of obedience, order and pre-established paths, the other marked by the diversity and complexity of social facts, and in keeping with the paradigm shift in the concept of science knowledge and c) promoting innovation in the public university in Venezuela, through its collective mobilization is that habituation to the dialogue, shared knowledge, teamwork and co-opetition networks.
Keywords: university research culture; job skills; networks coopetition